Leveraging Geodetic GPS Receivers for Ionospheric Scintillation Science. Issue 11 (21st November 2020) - Mrak, Sebastijan; Semeter, Joshua; Nishimura, Yukitoshi; Rodrigues, Fabiano S.; Coster, Anthea J.; Groves, Keith
Abstract: We demonstrate scintillation analysis from a network of geodetic Global Positioning System (GPS) receivers which provide data at 1‐second resolution. We introduce proxy phase ( σ T E C ) and amplitude ( S N R 4 ) scintillation indices and validate them against the rate of change of TEC index (ROTI) and S 4 . Additionally, we validate scintillation observations against a Connected Autonomous Space Environment Sensor scintillation receiver. We develop receiver‐dependent scintillation event thresholding using hardware‐dependent noise variance. We analyze 6 days adjacent to the 7–8 September 2017 geomagnetic storm, using 169 receivers covering magnetic latitudes between 15° and 65° in the American longitude sector. We leverage the available spatial sampling coverage to construct 2‐D maps of scintillation and present episodic evolution of scintillation intensifications during the storm. We show that low‐latitude and high‐latitude scintillation morphology match well‐established scintillation climatology patterns. At midlatitudes, spatiotemporal evolution of scintillation partially agrees with known scintillation patterns. Additionally, the results reveal previously undocumented midlatitude scintillation‐producing structures. The results provide an unprecedented view into the spatiotemporal development of scintillation‐producing plasma irregularities and provide a resource to further exploit scintillation evolution at large spatial scales. Key Points: Scintillation analysis of 1‐Hz geodetic receiver network covers 50° in latitude over the American longitude sector Proxy scintillation indices are derived and validated An event analysis reveals unprecedented storm time scintillation evolution over North American continent